Video capsule endoscopy to prospectively assess small bowel injury with celecoxib, naproxen plus omeprazole, and placebo - Goldstein, Jay L.; Eisen, Glenn M.; Lewis, Blair; Gralnek, Ian M.; Zlotnick, Steve; Fort, John G. (Clinical gastroenterology and hepatology, 2005)
Background & Aims: Data indicate that cyclooxygenase-2–specific inhibitors cause less gastroduodenal mucosal damage than nonspecific NSAIDS, but their effects on the small bowel mucosa are less well recognized. In a multicenter, double-blind, placebo-controlled trial with video capsule endoscopy (VCE) we prospectively evaluated the incidence of small bowel injury in healthy subjects treated with celecoxib compared to naproxen plus omeprazole. Methods: We randomly assigned subjects with normal baseline VCEs to celecoxib 200 mg twice daily (n = 120), naproxen 500 mg twice daily plus omeprazole 20 mg once daily (n = 118), or placebo (n = 118) for 2 weeks. The primary end point was the mean number of small bowel mucosal breaks per subject. Results: Baseline VCE found small bowel lesions in 13.8% (57/413) of screened subjects, who became ineligible for randomization. The mean number of small bowel mucosal breaks per subject and the percentage of subjects with these mucosal breaks were 2.99 ± 0.51, 55% for naproxen/omeprazole compared to 0.32 ± 0.10, 16% for celecoxib and 0.11 ± 0.04, 7% for placebo ( P < .001, both comparisons). The magnitude of the difference between celecoxib and placebo was small but statistically significant ( P = .04). Conclusions: Among healthy subjects with lesion-free baseline VCEs, celecoxib was associated with significantly fewer small bowel mucosal breaks than naproxen plus omeprazole. This study also showed that the background incidence of small bowel lesions in healthy adults is not insignificant and should be considered in future trials with VCE.